Thermodynamic analysis on a Kalina cycle based power and chilling refrigeration cogeneration cycle. (October 2019) - Zhang, Shaobo; Chen, Yaping; Wu, Jiafeng; Zhu, Zilong; Fang, Fang
Highlights: Kalina cycle based power and refrigeration cogeneration cycle (PPRA-KC) was studied. Refrigeration sub-branch is parallel to the power loop from outlet of mid-p absorber. To provide chilling water or ice making, refrigerant leads to mid or low-p absorbers. Factors impacting on comprehensive power recovery efficiency of PPRA-KC were studied. Optimal work concentration envelop line for regulating split fraction is presented. Abstract: A cogeneration system of power and refrigeration based on the triple-pressure Kalina cycle was proposed and investigated. A parallel branch of work solution is split at the outlet of the mid pressure absorber, and it forms a refrigeration sub-cycle to further utilize the heat source sufficiently and provide chilling water for air-conditioning refrigeration capacity. The split fraction for refrigeration f ref which determines the relative percentage of work solution flow rate for refrigeration (against power generation) can be altered according to user′s demand. The refrigerant from the evaporator is normally directed to the mid pressure absorber, and it can also be switched to the low pressure one to make ice for cooling load storage at off-peak time. The parameter analysis and optimization were conducted under temperatures of heat source of 450 °C and cooling water of 30 °C. The optimum f ref for the comprehensive power recovery efficiency rises with the decrease of the work concentration, and the lower work concentration has larger adjustable range of the f ref . The comprehensive power recovery efficiency reaches about 27.3 ± 0.05% at work concentrations of 0.474–0.5375 with evaporation temperature of 0.5–12 °C.